Oncogenic and Therapeutic Targeting of PTEN Loss in Bone Malignancies. Issue 9 (September 2015) - Xi, Yongming; Chen, Yan
ABSTRACT Being a tumor suppressor, PTEN functions as a dual‐specificity protein and phospholipid phosphatase and regulates a variety of cellular processes and signal transduction pathways. Loss of PTEN function has been detected frequently in different forms of cancers, such as breast, prostate and lung cancer, gastric and colon cancer, skin cancer, as well as endometrial carcinoma. In this review, we provide a summary of PTEN and its role in bone malignancies including bone metastases, multiple myeloma, and osteosarcoma, etc. We highlight the importance of PTEN loss leading to activation of the oncogenic PI3K/Akt/mTOR pathway in tumorigenesis and progression, which can be attributed to both genetic and non‐genetic alterations involving gene mutation, loss of heterozygosity, promoter hypermethylation, and microRNA mediated negative regulation. We also discuss the emerging therapeutic applications targeting PTEN loss for the treatment of these bone malignant diseases. J. Cell. Biochem. 116: 1837–1847, 2015. © 2015 Wiley Periodicals, Inc.